Transparansi dan Akuntabilitas Anggaran Pendapatan dan Belanja Desa (Studi Kasus di Desa Ngasem Kecematan Batealit Kabupaten Jepara) - Fatchur Rohman; Aci Relandani (Universitas Islam Nahdlatul Ulama Jepara, 2020)
This study aims to determine transparency and accountability in the implementation of the Village Income and Expenditure Budget in Ngasem Village, Batealit District, Jepara Regency. Because in Ngasem Village, Batealit Subdistrict, Jepara Regency, the Village Budget has always increased. In the Village Revenue and Expenditure Budget, priority is placed on village infrastructure. The data used in this study were obtained from data collection and carried out by direct observations in the field with interviews. The data analysis technique used in this study is a qualitative descriptive analysis with data processing methods with triangulation techniques. This interview technique was conducted directly with the Village Head, Village Secretary, Village Consultative Body, and Village Communities in Ngasem Village, Batealit District, Jepara Regency. The results of this study indicate that the Ngasem village has carried out transparency and accountability in the Village Budget of the 2018 budget year. In general the transparency and accountability in Ngasem Village has been in accordance with the provisions and has run well and smoothly.